Peran Guru Ngaji dalam Meningkatkan Karakter Santri pada Aspek Disiplin dan Tanggung Jawab di Taman Pendidikan Al-Qur’an (TPQ) Al-Muqorrobin Desa Panjangsari Kecamatan Gombong - Priyatno, Riski; Makmun, Syukron (IAINU Kebumen, 2025)
The objectives of this study are: 1.) To determine the role of the Koran teacher in improving the character of students in terms of discipline and responsibility at (TPQ) Al-Muqorrobin, Panjangsari Village, Gombong; 2) To determine the results of the role of the Koran teacher in improving the character of discipline and responsibility of students at (TPQ) Al-Muqorrobin, Panjangsari Village, Gombong. This study is a qualitative study. The subjects studied were the head of TPQ Al Muqorrobin, the Asatidz Council, students and parents (guardians of students). The data collection techniques used in this study were: observation, interviews, and documentation. The collected data were analyzed using the Miles and Huberman data model, namely; data condensation, data presentation, drawing conclusions. The results of the data analysis that has been done are: 1.) The role of the Koran teacher in improving the character of students in the aspects of discipline and responsibility as follows: a.) Teachers as educators, teachers as motivators, teachers as evaluators. 2.) The results of the role of Koran teachers in improving the character of discipline and responsibility: a.) Discipline Aspect: As educators; teachers make themselves role models, provide regulations on duty schedules, punishments. Teachers as motivators; Koran teachers provide stories of successful and influential Muslim figures in the world, give gifts and appreciation. Teachers as evaluators are proven by the existence of exams, report card distribution. b.) Responsibility Aspect; Teachers as educators; by way of exemplary behavior from teachers, implementation of duty schedules, doing assignments given by Koran teachers. Teachers as motivators; Koran teachers provide appreciation gifts for carrying out tasks, carrying out duty schedules and raising the spirit of students to diligently perform the five daily prayers. Teachers as evaluators; proven by knowing the success of students in carrying out their duties and responsibilities